Benchmarking Rolls-Royce’s Legacy and Low Volume Supply Chain against Industry Best Practices - Zaytsev, Alexander (2011)
This report details research conducted by Post Production Engine Services (PPES), a division of Rolls-Royce Group’s Gas Turbine Services business unit, to benchmark PPES’s legacy and low volume (L&LV) aftermarket supply chain management against the aftermarket supply chains of competitors and non-competitors in aerospace and other industries.